The Joint Effect of Paternal and Maternal Parenting Behaviors on School Engagement Among Chinese Adolescents: The Mediating Role of Mastery Goal - Wang, Juan; Shi, Xinxin; Yang, Ying; Zou, Hong; Zhang, Wenjuan; Xu, Qunxia (Frontiers in Psychology, 2019)
The present study aimed to explore the joint effect of paternal and maternal parenting behaviors on adolescent’s school engagement, and the mediating role of mastery goal. A total of 2,775 Chinese adolescent participants (55.3% females, mean age=15.70, SD=1.57) from two-parent families were recruited in 2014, who rated their perceptions of emotional warmth, behavioral guidance, harsh discipline of their father and mother, as well as their own mastery goal and school engagement. Results showed that paternal and maternal parenting behaviors had interaction effects on school engagement with different interaction patterns. Specifically, the interactions of both parents’ emotional warmth and both parents’ behavioral guidance displayed strengthening patterns, where one parent’s high emotional warmth or behavioral guidance enhanced the positive relationship between the corresponding parenting behavior of the other parent and adolescents’ school engagement. By contrast, the interaction of both parents’ harsh discipline displayed an interfering pattern, where one parent’s high level of harsh discipline reduced the negative relationship between harsh discipline of the other parent and school engagement. Further, all three interaction effects between father and mother on school engagement were mediated by mastery goal. These findings underline the importance of viewing family from a systematic perspective and the benefits of supportive parenting behavior of both parents.